Biotechnological and bio-industrial applications of alpha–l-rhamnosidase enzyme - Arshad Muhammad; Abdur Rahman Ansari; Sadia Javed; Mirza Imran Shahzad (Revista Politécnica, 2025)
α -L-rhamnosidase is an important biotechnology enzyme that is used in various foods, chemicals and pharmaceutical industries. The α-L-rhamnosidases (α- RHA) belong to a group of glycosyl hydrolases having biotechnological potential in the proesses occurring in industries, they stimulate the breakdown of terminal residues of α-L-rhamnose from many naturally occurring substances present in chemical industries. Flavonoid prunin is produced from Narignine by activity of α-L-rhamnosidase. It has anti-inflammatory and anti-viral activity against DNA or RNA viruses. It can be acquired from plants, animals and different microbial sources, such as (bacteria and yeast). Main sources of α-L-rhamnosidase are microbes, mainly filamentous fungi such as Aspergillus, Circinella, Eurotium, Fusarium, Penicillium, Rhizopus, and Trichoderma. The first bacterium α-L-rhamnosidase was screened from the genus Bacteroides. The other strains of bacteria that produce α-L-rhamnosidases are the heat-loving bacteria, Fusabacterium, Pseudoalteromonas, Ralstonia pickettii, Lactobacillus acidophilus, Pediococcus acidilactici, Clostridium stercorarium, and Sphingomonas paucimobis. Yeast rhymosidase is very important because it is produced in short fermentation, with increased shelf life, high thermal stability, the ability to retain flavor of juice and it is non-toxic for human consumption. For α-L-rhamnosidase purification, the centrifuge method is used, and various chemical products, such as ammonium sulphate, NaCl, are used. Finally, molecular weight (MW) of α-L-rhamnosidase has been determined by Gel Filtration Chromatography (GFC) and Sodium Dodecyl Sulfate Polyacrylamide Gel Electrophoresis (SDS-PAGE).